Influence of Moisture and Temperature Regimes on the Phytolith Assemblage Composition of Mountain Ecosystems of the Mid Latitudes: A Case Study From the Altay Mountains - Solomonova, Marina Y.; Blinnikov, Mikhail S.; Silantyeva, Marina M.; Speranskaja, Natalya Y. (Frontiers in Ecology and Evolution, 2019)
Background and Aims: Reconstruction of past ecosystems requires a robust understanding of modern deposition patterns and taphonomy for the proxies utilized. Recent advances in phytolith analysis have contributed to improved understanding of these processes, but many gaps remain. This study aims to test a few specific hypotheses that have been proposed by research outside the tropics in the Northern Hemisphere. Our study area focuses on the Northern Altay, a culturally important region, entirely within Russia, north of China, and Mongolia. We collected 60 phytolith assemblages from modern soils at 300 to 2,300 m a.s.l. elevations, sampled from 20 plots in triple replicates within 13 different plant communities. Detailed releves of these plant communities, including forests, meadows, steppe, and alpine tundra, were obtained during the summer of 2017. We used a locally derived scheme of V. P. Sedelnikov to assign studied communities to ecological categories based on moisture and temperature availability. Methods: Standard oxidation and heavy liquid flotation methods of extraction were used. Morphotypes were counted under 400–1,000x magnification on an optical microscope. We used a two-tier approach to phytolith morphotypes classification: a detailed one with over 40 morphotypes included and a shorter one with only sums of selected morphotypes. The former approach can produce some interesting results, such as using various types of rondels (e.g., pyramidal vs. keeled) or large vs. small lanceolate (trichomes). Using sums may be more widely applicable, because the researchers can replicate these results better and less training is needed. However, there are fewer diagnostic options with the sums approach. Key Results: Our results, using discriminant analysis, canonical correspondence analysis and other multivariate statistical methods, confirm earlier studies, both in the region and elsewhere that despite redundancy in phytolith distributions in soils, there are some selected morphotypes that can reliably distinguish communities at various positions along elevational, moisture, and temperature gradients. We developed a regionally diagnostic key that allows researchers to quickly identify various plant communities based on their phytolith assemblages in soils. Conclusions: Seven of 13 regionally important communities at medium elevations in the Altay Mountains can be distinguished by using aggregated and more detailed phytolith morphotypes.